Linking mathematics and language : practical classroom activities - Mccallum, Richard; Whitlow, Robert (Ontario : Pippin publishing limited, 1994)
A teaching principal and a university professor have joined forces to provide teachers with a set of introductory activities in mathematics for children 12 years and under, using language instruction as a tool for the development of mathematical concepts.
includes bibliographical references.
Keywords: Mathematics -- Study and teaching (Elementary); Reading (Elementary); English language -- Study and teaching (Elementary)